From rugby to basketball: a comparative analysis on the implementation of mixed ability - Elipe-Lorenzo, P.; da-Silva, C.; Diez-Fernández, P.; Ruibal-Lista, B.; Saavedra-García, M.; López-García, S. (Frontiers in Sports and Active Living, 2026)
Introduction: